Inhibition of the Mycobacterium tuberculosis enoyl acyl carrier protein reductase InhA by arylamides - He, Xin (2007)
InhA, the enoyl acyl carrier protein reductase (ENR) from Mycobacterium tuberculosis, is one of the key enzymes involved in the type II fatty acid biosynthesis pathway of M. tuberculosis. We report here the discovery, through high-throughput screening, of a series of arylamides as a novel class of potent InhA inhibitors. These direct InhA inhibitors require no mycobacterial enzymatic activation and thus circumvent the resistance mechanism to antitubercular prodrugs such as INH and ETA that is most commonly observed in drug-resistant clinical isolates. The crystal structure of InhA complexed with one representative inhibitor reveals the binding mode of the inhibitor within the InhA active site. Further optimization through a microtiter synthesis strategy followed by in situ activity screening led to the discovery of a potent InhA inhibitor with in vitro IC(50) = 90 nM, representing a 34-fold potency improvement over the lead compound.